2020
DOI: 10.1126/sciadv.aba9471
|View full text |Cite
|
Sign up to set email alerts
|

Surface slip on rotating graphene membrane enables the temporal selectivity that breaks the permeability-selectivity trade-off

Abstract: Membrane separation technology is dictated by the permeability-selectivity trade-off rule, because selectivity relies on membrane pore size being smaller than that of hydrated ions. We discovered a previously unknown mechanism that breaks the permeability-selectivity trade-off in using a rotating nanoporous graphene membrane with pores of 2 to 4 nanometers in diameter. The results show that the rotating membrane exhibits almost 100% salt rejection even when the pore size is larger than that of hydrated ions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 54 publications
2
37
0
Order By: Relevance
“…It has been shown that irreversible resistance arises in the short and initial period of the process. The efficiency is determined by reversible resistance, confirmed by the literature [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The values of individual resistances are much higher, relating to the values in other membrane processes.…”
Section: Resultssupporting
confidence: 65%
“…It has been shown that irreversible resistance arises in the short and initial period of the process. The efficiency is determined by reversible resistance, confirmed by the literature [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The values of individual resistances are much higher, relating to the values in other membrane processes.…”
Section: Resultssupporting
confidence: 65%
“…These porous frameworks transform into the membranes by various means, such as the contra-diffusion process, [2,6,7] spin coating method, castings with a doctor blade, vacuum filtration method, electrochemical depositions, [3,8] and secondary growth method. Besides the frameworks-integrated nanostructured IEMs, carbon nanotubes (CNTs) and graphene nanosheets [9] also remained useful to fabricate energyefficient ion-exchange membranes.…”
Section: Nanostructuredmentioning
confidence: 99%
“…Membrane performance in RO systems is the top choice by the water-treatment industry leaders due to low-energy consumption; application under normal conditions; ease to be combined (hybridized) with other operations; requiring no optional additives; simple and compact membrane module design specifications; and ease of utilizing in its operation [ 18 , 19 ]. For example, two studies by Zhang [ 20 , 21 ] reported that the use of rotating graphene nanoporous membranes with pores of diameter 2 to 4 nanometers successfully performed almost 100% salt rejection by using the RO system.…”
Section: Ro Membranes In Desalination Technologies and Their Novelmentioning
confidence: 99%